Qur'anic Critique of Exploitative Anthropocentrism: Exegesis of Verses on Land and Nature in the Context of Raja Ampat Mining - Ismail; Sukron, Mokhamad (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This article explores the ethical foundations of the Qur'an in addressing ecological degradation resulting from mining activities in protected areas, with particular attention to the case of nickel extraction in Raja Ampat. Employing a thematic and contextual hermeneutical approach, this library-based study analyzes four key Qur'anic verses (Hūd [11]: 61, Al-Baqarah [2]: 30, Ar-Rūm [30]: 41, and Ar-Raḥmān [55]: 7–9) which articulate the notions of land, human trusteeship (khalīfah), corruption (fasād), and ecological balance (mīzān). The analysis finds that classical anthropocentric interpretations often overlook ecological responsibility and fail to confront systemic exploitation. By integrating perspectives from contemporary Islamic eco-theology and the objectives of Islamic law (maqāṣid al-sharī‘ah), the study reinterprets these verses as a theological critique of extractive capitalism and as a foundation for an ethical framework centered on environmental justice. It concludes that the Qur'an offers a critical discourse against ecological destruction and calls for a prophetic shift in tafsir towards sustainability, justice, and the preservation of creation. This research contributes to the development of an interdisciplinary ecological hermeneutics within Islamic scholarship, offering timely relevance to the climate and ecological crises of the 21st century.